Wacana Islam di Facebook Jabatan-jabatan Mufti Malaysia - Muhamad Faisal Ashaari,; Rosmawati Mohamad Rasit,; Zainab Ismail,; Mohammad Ismath Ramzy, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The fatwa institution is an authoritative religious institution in issuing Islamic laws in Malaysia. However, the authoritative bodies in the virtual world are exposed to various challenges including open critiques. Until December 2018, not all departments of mufti in Malaysia are actively using Facebook, but some departments do not have Facebook account. This article analyzes the extent to which Facebook Departments of Mufti enter the public sphere, which is a form of open discussion. Therefore, this article discusses how the Departments of Mufti in Malaysia brings up the discourse about Islam on Facebook. This is a case study design using content analysis to check postings sent to Facebook. The design of this study is a case study focusing on the Facebook page of the Departments of Mufti in Malaysia. Data were collected from January to September 2018 for Facebook with less than 100 posts while those with over 100 posts were collected only from September 2018. The pro-active page in issuing Islamic laws on all issues is Wilayah Persekutuan and Perak can be considered as active. The discourse and propagation of Islamic laws through Facebook could not be much given by Mufti Departments and some of them even do not have a Facebook. The departments seem incompetent to conduct Islamic Discourse in Malaysia public sphere.